HIV and AIDS law and policy in Nigeria - Ortuanya, Simon Uchenna (Malthouse Press, 2022)
This book provides a detailed and timely analysis of key regulatory and legal issues arising in the context of HIV and AIDS. The ten chapters cover the core issues central to an understanding of law and public health as concerns AIDS. Whilst the book focuses on how Nigerian law applies to HIV and AIDS, the author draws heavily on materials from other jurisdictions. There are many parallels that exist between the application of law and governance considerations in the AIDS pandemic that resonate with other infectious diseases including Covid-19, therefore the book is widely relevant to public health law in communicable disease contexts. Topics covered: overview and origin of the HIV and AIDS epidemic; legal and institutional framework of the HIV and AIDS epidemic in Nigeria; human rights and the epidemic; decriminalisation of HIV and AIDS in Nigeria; HIV and AIDS and vulnerable groups; HIV and AIDS and patents; HIV and AIDS and sports; international organisations and programmes on HIV; judicial responses to HIV and AIDS; and global pandemics and control.